2012
DOI: 10.1016/j.vhri.2012.10.001
|View full text |Cite
|
Sign up to set email alerts
|

An Estimate of the Cost of Hepatitis C Treatment for the Brazilian Health System

Abstract: In Brazil, antiviral drugs are the most expensive component of hepatitis C treatment. The cost of follow-up and support to patients is minimal compared with the cost of antiviral drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…These costs were higher than direct costs of other chronic condition in Brazilian populations, such as diabetes (USD 1,012) (44) , and non-melanoma skin cancer (BRL 1,172) (45) ; but lower than rheumatoid arthritis (BRL 19,860.16) (46) . In addition, the results showed that drug treatment was the costliest component, accounting for 95.9% of total HCV costs; accordingly, a Brazilian study conducted prior to the incorporation of protease inhibitors have shown that drug treatment represented 88.2% of the total costs (47) .…”
Section: Discussionmentioning
confidence: 99%
“…These costs were higher than direct costs of other chronic condition in Brazilian populations, such as diabetes (USD 1,012) (44) , and non-melanoma skin cancer (BRL 1,172) (45) ; but lower than rheumatoid arthritis (BRL 19,860.16) (46) . In addition, the results showed that drug treatment was the costliest component, accounting for 95.9% of total HCV costs; accordingly, a Brazilian study conducted prior to the incorporation of protease inhibitors have shown that drug treatment represented 88.2% of the total costs (47) .…”
Section: Discussionmentioning
confidence: 99%
“…The analyses performed here excluded the costs of antiviral and co-medications, which typically constitute the largest part of the total treatment costs for HCV patients [ 34 , 35 ]. The reason for this was that the first aim of this study was to identify patient and treatment characteristics that would influence MRU—and thus the total cost of care—so that these could be better managed, as in other therapeutic areas, such as oncology, diabetes and human immunodeficiency virus (HIV) infection [ 36 – 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The MRU-related costs in our study were within the ranges of treatment costs previously published. In the German context, the costs for outpatient visits were €355 (£293), which represent about 2 % of the total treatment cost for HCV patients [ 34 , 35 , 39 ]. Athanasakis et al [ 40 ] estimated the annual cost per patient for patients with a METAVIR score of F0–F3 to be €643 (£530), excluding the cost of medications.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-virals are among the main therapeutic classes of the cohort studied, including anti-retroviral agents and drugs for hepatitis. Viral hepatitis is currently a public health concern and the drug access program has been expanded through the specialized component of pharmaceutical assistance 38 . Brazil has shown sustained advances in biomedical, clinical and epidemiological research on issues involving the prevention and treatment of infectious diseases 35 .…”
Section: Discussionmentioning
confidence: 99%